2016
DOI: 10.5125/jkaoms.2016.42.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Benign cementoblastoma of the anterior mandible: an unusual case report

Abstract: A benign cementoblastoma, which is another name for a true cementoma, is a rare neoplasm that develops from odontogenic ectomesenchyme. It is characterized by a mineralized mass attached to the apex of the root produced by neoplastic cementoblasts. More than 75% of cases arise in the mandible, with 90% of them manifesting in the molar and premolar regions. This neoplasm occurs most commonly in children and young adults, with males being affected slightly more than females. Radiographically, the tumor is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…This is now the oldest reported age occurrence for cementoblastoma in the Western population. Pain, tenderness and swelling are present in most cases of cementoblastoma [2,8,11]; however, some cases can be asymptomatic [1,4,6,7,8]. In the present case, the tooth was vital and asymptomatic, however, unlike most cases described in the literature, no swelling was observed and the lesion was only detected from the radiographic examination.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…This is now the oldest reported age occurrence for cementoblastoma in the Western population. Pain, tenderness and swelling are present in most cases of cementoblastoma [2,8,11]; however, some cases can be asymptomatic [1,4,6,7,8]. In the present case, the tooth was vital and asymptomatic, however, unlike most cases described in the literature, no swelling was observed and the lesion was only detected from the radiographic examination.…”
Section: Discussionmentioning
confidence: 50%
“…The typical clinical presentation of cementoblastoma includes: male or female under 30-years-old, can be painful or asymptomatic, swelling, located in the premolar/molar region, [1,4,6,10,11,12,13], more frequently in the mandible [1,4,6,7,10,12,11,12,13,14,15,16]. Previous studies have reported the occurrence of cementoblastoma in the right maxillary and mandibular canine [6,8], right upper posterior tooth region [1], maxillary central incisor [7], mandibular first molar [14] and maxillary right first molar [4]. In the case described here, a tumor was identified in the left posterior maxilla of a 52-year-old female.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations